Interdisciplinary teacher education in the teaching of exact sciences and nature: the importance of interdisciplinarity (Research, Society and Development, 2020)
The present work presents an attitude and conduct based on concepts that are transcendent to the exchange of various knowledge based on a bibliographic survey in which thinkers on the theme present their contributions. The interdisciplinary requirement imposes on each specialist that transcends his own specialty and becomes aware of his own limits to welcome the contribution of other disciplines. Interdisciplinarity configures the guiding spirit of a new system to expand the overall view, the convergence of ideas, and capable of replacing that of dissociation so present in the sciences. A reading of the general concepts and epistemological aspects and one can learn the interdisciplinary skills consistent with the activities of teaching, researching and producing knowledge. The propositions, presented here, cooperate as a reference to better signal a critical reflection. It is necessary to understand, with urgency, that interdisciplinarity is a new strategy in the work of epistemological characterization, assuming the combined effort of several disciplines to achieve the meanings of an object of study.